Analisis Konsep Teritorial Ruang Rumah Tradisional Bangsawan Bugis Di Bone Sulawesi Selatan Dalam Penerapan Merdeka Belajar Kampus Merdeka Bidang Penelitian - Akbar Andi Muhammad; Setiawati Nur; Ishak Gani (Universitas Muslim Indonesia, 2022)
The application of Merdeka Learning Campus Merdeka (MBKM) in this field of research analyzes the traditional architecture of the Bugis tribe which is closely related to the history of the Bugis kingdom in the past, where the City of Bone is the base in South Sulawesi. The architecture of the traditional house of the Bugis Bone nobility at that time was strongly influenced by the social stratification that prevailed in their society. The configuration of the spaces has its own characteristics and is able to provide expression as an element of the typical culture of an area by making distinctions between spaces based on social stratification to form a territory of cultural cognition. The purpose of this study is to analyze the concept of territorial space that affects the architectural characteristics of the traditional house which is reviewed based on the pattern of the Spatial system and the Physical system as well as the Stylistic system. The scope of this research is limited to the basis of the Bugis kingdom in Bone Regency, South Sulawesi. This study uses a qualitative methodology with a phenemological paradigm approach, then analyzes in detail the typomorphology of the spatial configuration of each sample of the Bugis Bone nobility's house as a tool to measure the characteristics of the architectural space. The results of the research on the spatial concept of the Bugis Bone noble house is a physical expression that is closely related to his identity which is influenced by socio-cultural factors of the Bugis society in Bone at that time.